Mediocre growth in the Euro area: Is governance part of the answer? - Jean Pisani-Ferry (Bruegel, 2006)
Jean Pisani-Ferry's note was prepared for the European Parliament-National Parliaments Debate on How to Raise Growth in the Euro Area? in Brussels.
Keywords: 330; Wirtschaftswachstum; Wachstumspolitik; Europäische Wirtschafts- und Währungsunion; EU-Staaten